Tindakan Keberanian “Mengatakan Tidak Pada Rokok”: Upaya Membentuk Kesadaran Bahaya Merokok Pada Anak Melalui Penanaman Nilai-Nilai Pendidikan Agama Kristen - Yermias Eliasar Alunat; Yosias Metuduan; Iszak Jacub Lesirolo; Paulus Lumbaa; Dellin Pentury; Suadin Zai; Elieser R. Marampa (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
The young generation is currently in a state of emergency considering that the smoking phenomenon has spread to remote areas, which has an impact and influence on children during their growth and development and the ecosystem for human survival is disrupted. The aim of writing this study is to provide understanding in forming awareness about the dangers of smoking for children with a contribution approach to Christian religious education. The method used in this research is a descriptive qualitative approach with a literature review method through books, journal articles and websites as references in data collection. The results show that the contribution of Christian religious education plays an important role in the process of preparing children to face life's challenges within the framework of Christian values and principles. In this case, it can involve the role of parents, society, churches, schools and other communities in strengthening children's understanding of the value of the body and the dangers of smoking. Thus, this can help children not become addicted to cigarettes and build a wall of resistance against consuming cigarettes.